Anti-tumor efficacy of new 7α-substituted androstanes as aromatase inhibitors in hormone-sensitive and resistant breast cancer cells. Issue 171 (July 2017) - Amaral, Cristina; Varela, Carla L.; Maurício, João; Sobral, Ana Filipa; Costa, Saul C.; Roleira, Fernanda M.F.; Tavares-da-Silva, Elisiário J.; Correia-da-Silva, Georgina; Teixeira, Natércia
Highlights: New 7α-substituted steroidal molecules are potent aromatase inhibitors (AIs) in ER + breast cancer cells. The AIs can inhibit ER + breast cancer cell growth and sensitize resistant breast cancer cells. New structure-activity relationships for 7α-substituted steroidal compounds were established. Chemical modifications in steroidal scaffold that improve aromatase inhibition and anti-tumor efficacy were elucidated. Abstract: The majority of breast cancer cases are estrogen receptor positive (ER + ). Although, third-generation aromatase inhibitors (AIs) are used as first-line treatment in post-menopausal women, they cause endocrine resistance and bone loss, which limits their success. Therefore, there is a demand to discover new potent molecules, with less toxicity that can circumvent these drawbacks. Our group has previously demonstrated that new 7α-substituted steroidal molecules, 7α-(2ξ, 3ξ-epoxypropyl)androsta-1, 4-diene-3, 17-dione(3), 7α-allylandrost-4-ene-3, 17-dione(6), 7α-allylandrost-4-en-17-one(9), 7α-allyl-3-oxoandrosta-1, 4-dien-17β-ol(10) and 7α-allylandrosta-1, 4-diene-3, 17-dione(12) are potent AIs in placental microsomes. In this work, it was investigated their anti-aromatase activity and in vitro effects in sensitive and resistant breast cancer cells. All the steroids efficiently inhibit aromatase in breast cancer cells, allowing to establish new structure-activity relationships for this class of compounds. Moreover, the new AIs can inhibit breast cancer cell growth, by causing cell cycle arrest and apoptosis. The effects of AIs3 and12 on sensitive cells were dependent on aromatase inhibition and androgen receptor (AR), while for AI9 and AI10 were AR- and ER-dependent, respectively. In addition, it was shown that all the AIs can sensitize resistant cancer cells being their behavior similar to the sensitive cells. In summary, this study contributes to the understanding of the structural modifications in steroidal scaffold that are translated into better aromatase inhibition and anti-tumor properties, providing important information for the rational design/synthesis of more effective AIs. In addition, allowed the discovery of new potent 7α-substituted androstane molecules to inhibit tumor growth and prevent endocrine resistance.